The Effect of U.S. Country‐by‐Country Reporting on U.S. Multinationals’ Tax‐Motivated Income Shifting and Real Activities - NESSA, MICHELLE L.; PERSSON, ANH V.; SONG, JANE Z.; TOWERY, ERIN M.; VERNON, MARY E. (Journal of Accounting Research, 2025)
ABSTRACT The Organization for Economic Cooperation and Development introduced country‐by‐country reporting (CbCR) for multinational enterprises (MNEs) to help tax authorities combat tax‐motivated income shifting. This study uses confidential U.S. tax administrative data from 2011 to 2018 to examine the effect of U.S. CbCR adoption on the tax‐motivated income shifting and real activities of U.S. MNEs. We first document that while U.S. CbCR provides the Internal Revenue Service with incremental information about the location of U.S. MNEs’ global activities relative to existing U.S. tax return disclosures, substantial overlap exists between U.S. CbCR and existing disclosures. In contrast with prior CbCR studies in cross‐country settings, we fail to find evidence of a change in U.S. MNEs’ tax‐motivated income shifting or a reallocation of real activities based on tax incentives in response to U.S. CbCR using multiple empirical approaches. Overall, our study leverages U.S. tax administrative data to provide insights into the impact of the CbCR initiative on U.S. MNEs.